Combined production of power and syngas in an internal combustion engine – Experiments and simulations in SI and HCCI mode. (1st March 2018) - Wiemann, Sebastian; Hegner, Robert; Atakan, Burak; Schulz, Christof; Kaiser, Sebastian A.
Abstract: In this work, an internal combustion engine is used as a reactor for partial oxidation to produce syngas together with mechanical work. Experiments were performed in a single-cylinder engine operated on methane/air. Spark-ignition (SI) and homogeneous-charge compression-ignition (HCCI) were investigated. For HCCI, 5 mol% n-heptane were added to the fuel to reduce auto-ignition temperatures. With spark ignition at ϕ = 1.56, the product gas contained up to 8.6 mol% CO and 7.7 mol% H2 at 71.5% exergetic efficiency, while at ϕ = 0.72 roughly the same mechanical work was generated, but with only 42.5% exergetic efficiency. Under the richer conditions achievable in HCCI combustion, syngas content increased to 15.8 mol% CO and 17.9 mol% H2, and the exergetic efficiency to 81.5%. A homogeneous single-zone model coupled with a detailed reaction mechanism was used to simulate the process. The experimental results and the simulation were in good agreement for operating points without frequent misfires.